The purpose, management and governance of IFIs: A case study of ambiguity - Pasquale Lucio Scandizzo (EIB Papers, 1998)
The international economic order pursued by the Bretton Woods 'founding fathers' was based on the idea that a combination of different international institutions would be needed to keep the world financial system from degenerating into periodic and destructive crises (Mikesell, 1994). Following the creation of the World Bank, a number of international financial institutions (IFIs) were established, sharing the Bretton Woods model as a means of achieving co-operation among lenders and borrowers and, at the same time, differing in regional orientation and modes of behaviour. The three regional development institutes - the Inter-American Development Bank, the Asian Development Bank and the African Development Bank - followed more closely the World Bank course. The European Investment Bank (EIB) and, much later on, the European Bank for Reconstruction and Development (EBRD), on the other hand, developed their own approach to international co-operation and development finance.
Keywords: 330; Entwicklungsbank; Entwicklungsorganisation; Welt